Soil Exploitation and Environmental Impacts of Brick Making in Wasur 2 Merauke Regency - Zegovia Parera (Jurnal Hukum Volkgeist, 2021)
Merauke Regency is a coastal area with muddy soil conditions. sand and gravel materials, because of these conditions the community and housing business actors use red bricks as material for development in Merauke district which is currently being carried out in all sectors of life, especially building and housing construction. This research was conducted to determine the process of mining soil for the brick-making process and the impact of mining on the surrounding physical environment. How is the environmental permit granted by the Government for the exploitation of brick-making land and how is the Merauke Regency Government's supervision of mining. From the results of this study, it can be concluded that, the brick mining process carried out by brick craftsmen in Wasur 2 does not have a production permit from the relevant Government Agencies and there is no environmental study from the Merauke Regency Environmental Agency and there is no regular supervision from the Government. and the Environment Agency of Merauke Regency so that land exploitation activities are still ongoing which will have an impact on soil degradation and environmental damage and can cause a decrease in the function of top soil which is rich in nutrients as a function of land cover vegetation which can change the structure of the soil and the area. will become increasingly dry and unproductive.